Prognostic impact of mucin spread, tumor cell spread, and invasive size in invasive mucinous adenocarcinoma of the lung. (August 2020) - Saito, Tomohito; Tsuta, Koji; Honda, Osamu; Ishida, Mitsuaki; Yamaka, Ryosuke; Tanaka, Noriyuki; Ishida, Kaori; Utsumi, Takahiro; Maru, Natsumi; Matsui, Hiroshi; Taniguchi, Yohei; Hino, Haruaki; et al.
Highlights: The impact of pathologic measures of invasive mucinous adenocarcinoma is assessed. Mucin spread size is a reasonable pathological T determinant. Tumor cell spread/ invasive size are candidate pathological T determinants. Tumor cell spread/ invasive size are discordant with radiologic solid size. Abstract: Objectives: The pathological T descriptor of lung invasive mucinous adenocarcinoma (IMA) is currently defined according to mucin spread, whereas that of lung non-mucinous adenocarcinoma is defined according to invasive lesion. This study aimed to evaluate and compare the prognostic impact of mucin spread, tumor cell spread, and invasive lesion in patients with lung IMA. Materials and Methods: Twenty-seven patients with completely resected pT1-4N0M0 IMA were evaluated. The radiological size (RS), mucin spread size (MS), tumor cell spread size (TS), and invasive size (IS) of the primary tumors were determined. Cox proportional hazards models were used to estimate recurrence-free survival (RFS). Because the MS, TS, and IS may be mutually confounding factors, they were evaluated using separate multivariate models including potential prognostic factors identified as significant on univariate analyses. Results: The median postoperative follow-up time was 4.9 years. TS and IS were significantly smaller than RS by a median of 0.3 cm ( p  = 0.027) and 1.4 cm ( p  < 0.0001), whereas MS and RS were not significantly different ( p  > 0.999). Univariate analyses identified T descriptors defined by MS, TS, and IS as potentially negative prognostic factors, in addition to age >75 years and carcinoembryonic antigen >5 ng/mL. Multivariate analyses revealed that T factors defined by MS, TS, and IS were significant predictors of RFS ( p  < 0.0001, p  = 0.0002, and p  = 0.0067, respectively). Conclusion: MS is a reasonable determinant of the pathological T descriptor of lung IMA. TS and IS are potential candidates, although they remain discordant with RS. If the TS or IS is to be considered a candidate for the pathological T descriptor of lung IMA, the discordance with RS should first be resolved. If IS is used to define pathological T factor, clear criteria for mucinous AIS/MIA with IMA features should be developed.